Identification of The Bactericide Active Fraction on Zingiber gramineum Blume Bark - I Made Dira Swantara (Jurnal ILMU DASAR, 2009)
Bactericide fraction as been isolated and identified from Zingiber gramineum Blume bark. The isolation carried out using partition by n-hexane, chloroform, and ethyl acetate eluent. The extract bactericide active (ethyl acetate extract) as  been isolated using column chromatograpic method by benzene-chloroform (3:2) eluen system. The activity test of that isolate using Micrococcus luteus and Eschericia coli. The chemical  structure of the compound was identified  using gas chromatography-spectroscopy massa with Wiley 275.L library. The active fraction for E. coli contain hexadecanoic acid, ethyl ester;  linoleic acid, ethyl ester; oleic acid, ethyl ester; and octadecanoic acid, ethyl ester. The active fraction for M. luteus contain octadecnoic acid; 9,12-octadecadienoic acid; octadec-9-enoic acid; and hexadioic acid, dioctyl ester.